Characterization of Antigen-Induced CD4+ T-Cell Senescence in Multiple Sclerosis - Tomas-Ojer, Paula; Puthenparampil, Marco; Cruciani, Carolina; Docampo, María José; Martin, Roland; Sospedra, Mireia (Frontiers in Neurology, 2022)
Antigen-induced T cell exhaustion and T cell senescence are peripheral regulatory mechanisms that control effector T cell responses. Markers of exhaustion and senescence on T cells indicate previous activation by repetitive stimulation with specific antigens. Malignant tumors are accompanied by enhanced T cell exhaustion and T cell senescence resulting in immune evasion while these control mechanisms might be diminished in autoimmune diseases including multiple sclerosis (MS). To better understand the involvement of antigen-induced T cell senescence in controlling CD4+ T cell-mediated autoimmune responses in MS, we have analyzed the re-expression of CD45RA and the downregulation of CD28 and CD27 molecules as markers of antigen-induced T cell senescence in fresh cerebrospinal fluid (CSF)-infiltrating and paired circulating T cells from MS patients. Patients with different levels of CD4+ T cell senescence were identified and characterized regarding demographic and clinical features as well as intrathecal markers of neurodegeneration. CD4+ T cell senescence was also analyzed in control patients to explore a putative deficit of this regulatory mechanism in MS. Our study shows heterogeneity of markers of CD4+ T cell senescence in MS patients. Patients with high levels of CD4+ T cell senescence in peripheral blood showed increased frequencies of CSF-infiltrating CD28+ CD27- EM CD4+ T cells with a pro-inflammatory Th1 functional phenotype. The correlation of these cells with the intrathecal levels of neurofilament light chain, a marker of neurodegeneration, suggests their relevance in disease pathogenesis and the involvement of T cell senescence in their regulation. Markers of antigen-induced T senescence therefore show promise as a tool to identify pathogenic CD4+ T cells in MS patients.